The determinants of food satisfaction among domestic visitors: the case of gastronomic tourism in kelantan - Fikri Hakim Zaini; Hadzleen Nur Syarfaqila Hamden; Haniff Safwan Razali; Haslinda Mohd Ariffin (2023)
Measuring tourist food satisfaction has become more crucial since the gastronomic tourism sector involves travellers’ desire to have authentic and unique eating experiences, which is presently a growing trend in the tourism business. As one of Malaysia's most well-known destinations for food tourism, Kelantan was chosen for the study. The objective of this study is to see if there is a link between food related motivation, involvement, perceived value, and food satisfaction among domestic tourists. This study used a quantitative survey of tourists as determinants of food satisfaction in Kelantan. A total of 200 respondents participated to answer all questions in this survey. Food related motivation, involvement, and perceived value have a significant relationship with food satisfaction among domestic tourists. So, all hypotheses are supported. Therefore, stakeholders such as state government, businesses or non-governmental organisations must continue to make efforts to create more appealing destination in Kelantan with variety and tasty cuisine in order to initiate food satisfaction among domestic tourists. Keywords: Local food, Food-related motivation, Local food involvement, Food satisfaction, Food tourism, Perceived value, Gastronomic tourism.